Соціальна реабілітація : робоча програма - Петровська, Катерина Володимирівна (БДПУ, 2023)
Робоча програма з дисципліни "Соціальна реабілітація" для здобувачів другого магістерського рівня вищої освіти спеціальності 231 Соціальна робота освітньо-професійної програми "Поствоєнна соціально-психологічна реабілітація".
Work programme "Social rehabilitation"
The work program in the discipline "Social Rehabilitation" for applicants for the second master's level of higher education specialty 231 Social work of the educational and professional program "Post-war socio-psychological rehabilitation."
Keywords: реабілітація; соціальна реабілітація; реабілітаційні програми; установи реабілітації; rehabilitation; social rehabilitation; rehabilitation programs; rehabilitation institutions